General Movement assessment and neurodevelopmental trajectory in extremely preterm infants with hypothyroxinaemia of prematurity (THOP). (May 2020) - Goel, Dimple; Luig, Melissa; Maheshwari, Rajesh; D'Cruz, Daphne; Goyen, Traci-Anne
Abstract: Background: Transient hypothyroxinaemia of prematurity (THOP) has been associated with neurodevelopmental deficits with a paucity of literature leading to variable practice. Aim: Evaluation of the relationship between free T4 (fT4) levels at 2 weeks after birth and early markers of neurodevelopmental outcome. Study design: A retrospective study of prospectively collected data from infants born <29 weeks' gestation, admitted to NICU between January 2012 and December 2014. The primary outcomes were the relationship between fT4 levels at 2 weeks, Prechtl General Movement Assessment (GMA) at 36 weeks and 3 months postterm age, and Bayley Scales of Infant Development (BSID-III) at 2 years postterm age. Secondary outcomes were survival free of disability and other neonatal morbidities. Results: Of 122 infants, 101 infants had normal fT4 levels (No-THOP) and 21 had fT4 levels >1SD below the mean (THOP group). There was increased frequency of abnormal GMA in the No-THOP group compared with the THOP group at 36 weeks (abnormal writhing GMs: 43% vs 21%, p = 0.15) and 3 months corrected age (absent fidgety GMs: 7.6% vs 0%, p = 0.36), though not statistically significant. The neurodevelopmental outcome was worse in the No-THOP group compared with the THOP group with significantly lower mean cognitive and motor scores at 2 year of corrected age (90 ± 13.8 vs 100 ± 8.3, p = 0.01 and 91 ± 15.2 vs 100 ± 13.2, p = 0.04 respectively). Conclusions: This is the first report describing General Movements (GMs) in preterm infants with THOP. We found worse neurodevelopmental outcome in No-THOP infants reflected by significantly worse cognitive and motor outcomes at 2 years corrected age. Highlights: First study examining the effect of THOP on neurodevelopmental trajectory from 36 weeks - 2 years corrected age in preterm infants The level of free T4 after birth is directly related to gestational age at birth Lower free T4 levels are possibly a neuro-protective adaptive mechanism in extremely preterm infants. Worse neurodevelopmental outcomes were seen at 36 weeks, 3 months and 2 year corrected age in infants with fT4 in normal range.